1998
DOI: 10.1021/np970277l
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Effects of N-Containing Sugars from Xanthocercis zambesiaca, Morus bombycis, Aglaonema treubii, and Castanospermum australe in Streptozotocin-Diabetic Mice

Abstract: The aqueous MeOH extract of the leaves and root of Xanthocercis zambesiaca (Leguminosae) and eight structurally related nitrogen-containing sugars, fagomine (1), 4-O-beta-D-glucopyranosylfagomine (2), 3-O-beta-D-glucopyranosylfagomine (3), 3-epifagomine (4), 2,5-dideoxy-2,5-imino-D-mannitol (5), castanospermine (6), alpha-homonojirimycin (7), and 1-deoxynojirimycin (8) were evaluated for antihyperglycemic effects in streptozotocin (STZ)-diabetic mice. The insulin-releasing effects of 1 were also investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(83 citation statements)
references
References 14 publications
2
80
0
1
Order By: Relevance
“…It could effectively inhibit the postprandial hyperglycemia as a novel α-glucosidase activity inhibitor for diabetic therapy [8,11]. Decades ago, it had been found that 1-deoxynojirimycin (DNJ) was one of the alkaloids in mulberry strongly inhibiting α-glucosidase both in vitro and in vivo [44,45]. It was also reported that the hybrid of DNJ and polysaccharide from mulberry leaves may have antidiabetic activity by regulating the expression of the hepatic gluconeogenesis enzymes, glucokinase, phosphoenolpyruvate carboxykinase, and glucose-6-phosphatase [46].…”
Section: Discussionmentioning
confidence: 99%
“…It could effectively inhibit the postprandial hyperglycemia as a novel α-glucosidase activity inhibitor for diabetic therapy [8,11]. Decades ago, it had been found that 1-deoxynojirimycin (DNJ) was one of the alkaloids in mulberry strongly inhibiting α-glucosidase both in vitro and in vivo [44,45]. It was also reported that the hybrid of DNJ and polysaccharide from mulberry leaves may have antidiabetic activity by regulating the expression of the hepatic gluconeogenesis enzymes, glucokinase, phosphoenolpyruvate carboxykinase, and glucose-6-phosphatase [46].…”
Section: Discussionmentioning
confidence: 99%
“…The extract derived from mulberry leaves potentiated the pilocarpine-induced salivary flow which was correlated with antihyperglycemic effects . Fagomine from mulberry leaves increased the plasma insulin level in STZ-diabetic mice, and this insulin release by fagomine might partly contribute to the antihyperglycemic action (Nojima et al, 1998;Taniguchi et al, 1998). The maximum reduction in blood glucose of leaf extract was ob-served among fruit, trunk bark and root bark (Hosseinzadeh & Sadeghi, 1999).…”
mentioning
confidence: 99%
“…Several animal studies have been conducted to date. Nojima and co-workers showed that administration of mulberry leaf extract restored impaired glucose metabolism and hyperglycemic conditions in streptozotocin-induced diabetic mice (Nojima et al, 1998;Kimura et al, 1995). At present, various mulberry food products, including teas, powders, and tablets, are commercially available in Japan and many other countries.…”
Section: Mulberrymentioning
confidence: 99%